Hereditary breast cancer: review and current approach - Haddad, Cássio Furtini (Mastology, 2020)
Hereditary breast cancer is a complex and important condition, representing about 10% of all breast cancer cases. Identifying highrisk patients and possible carriers of pathogenic genetic variants with indication for genetic testing is an essential step to care for these patients and their families. Treatment can be influenced, both surgical and adjuvant, by the existence of mutation, providing the possibility of better results and preventive measures. In Brazil, access to oncogeneticists and genetic counseling is limited. Mastologists and their teams must be trained to identify and conduct the approach of these patients, with the objective of offering an adequate and preventive care, as well as early diagnostics. In the present study, a literature review of hereditary breast cancer aspects, diagnostic, and implications, in patients with and without breast cancer, was performed, aiming to assist in the proper management offered by mastologists, considering general and Brazilian characteristics.